PSXI-30 Impacts of hypocalcemia on physiological and productive responses of Holstein x Gir dairy cows. (7th December 2018) - Rodrigues, R; Cooke, R; Rodrigues, S; Bastos, L; Camargo, V; Gomes, K; Moraes Vasconcelos, J
Abstract: This study compared physiological and productive parameters in ¾ Holstein × ¼ Gir dairy cows classified as hypocalcemic or not during the first 5 d in milk (DIM). Non-lactating, multiparous, pregnant cows (n = 32) were enrolled in this experiment 21 d prior to expected date of calving. Cow BW and BCS were recorded weekly, and blood samples collected on d -21, -14, -9, -6, and -3 relative to expected calving. After calving (d 0), cow BW and BCS were recorded weekly and milk production was recorded daily until 30 DIM. Blood samples were collected during the first 5 DIM, as well as at 6, 9, 16, 23, and 30 DIM. Cows were classified with hypocalcemia when mean serum Ca during the first 5 DIM was ≤ 2.125 mmol/L. Hypocalcemic cows (n = 11) had less BCS and serum IGF-I concentrations at the beginning of the study compared with healthy cows (n = 21), which persisted until 30 DIM (main treatment effect, P ≤ 0.03). A tendency for a similar outcome (P = 0.10) was observed for serum insulin. Hypocalcemic cows had greater serum concentrations of cortisol at calving (P < 0.01), serum haptoglobin until 16 DIM (P < 0.01), and tended to have greater mean concentrations of non-esterified fatty acids postpartum (P = 0.10). No differences were detected (P ≥ 0.67) for cow BW and milk production, including milk yield adjusted to milk fat, total solids, and energy (P ≥ 0.41). Hypocalcemic cows tended to have (P ≤ 0.10) less milk fat, protein, lactose, total solids, but greater (P = 0.05) somatic cell count. Therefore, Holstein × Gir cows diagnosed with hypocalcemia had impaired energy status and transient increases in adrenocortical and acute-phase reactions, reduced concentration of milk components, and increased milk somatic cell count during the transition period. Key Words: